Electronic measurement of collaboration health within a central electronic knowledge platform. - Lok, Dawid Francois (My University, 2010)
In the keynote of Executive Workshop on the Aging Workforce in the Utility Industry held in April 2006 at Carnegie Mellon University in Pittsburgh, Erroll Davis highlighted the following fact: “The U.S. Bureau of Labour reports that the U.S. will face a shortage of 12 million qualified skilled workers by 2010.” (George, 2006). According to Krishna (2006) as many as 300,000 power utility workers within the U.S. are expected to retire over the next 15 years. Capturing and disseminating industry experience will be essential combined with effective communities of practice. These statement alone indicate why the virtual access to knowledgeable people will become a very important feature of any electronic knowledge platform (eKP). No longer is it practical to have a ratio of 1:1 in terms of students to mentors. Mentors are also not able to attend to the needs of apprentices entering the power industry. There has to be a balance between sharing the knowledge of a mentor in an explicit way (i.e. documents, decision support trees, questions and answers) and enabling knowledge workers seeking advice to contact the specialist when the available literature and tools are not self explanatory or doesn’t cover the particular problem. The challenge of today’s knowledge economy is the skills shortage and lack of sufficient people to mentor and train others on the job. The proof-of-concept (POC) presented in this dissertation is focussed on an electrical utility company in South Africa. Knowledge management is a multi-disciplinary field and touches on human and the technology aspects to address the problems experienced by knowledge management practitioners and managers. This dissertation focuses on how information technology (IT) could be used to assist in determining an electronic knowledge collaboration indicator that will give managers a tool to objectively measure and control retention of knowledge gained by individuals throughout their careers within an organisation. A central platform, namely Hyperwave, a commercially available software environment, combined with an effective search and indexing engine called “Autonomy” is used for the proof-of-concept (POC).